Arabic grammar as illustrated in elementary Modern Standard Arabic: A descriptive and critical study - Arif K. Abukhudairi (Journal of Modern Languages)
This paper intends to review Arabic Grammar as presented in Elementary Modern Standard Arabic by Peter Abboud and others. In the paper, I try to answer this question: can a grammarian study a grammar of a foreign language using the descriptive framework and terminology of his own language? It is necessary to note here that I do not claim that a grammarian cannot write on a grammar of a foreign language, because even in Arabic itself, the first and the best grammar book was written by a Persian.